Serum Folate of Less than 7.0 ng/mL is a Marker of Malnutrition. (28th October 2020) - Mattox, Samantha; Kozman, Diana; Singh, Gurmukh
Abstract: Folate is an essential nutrient that humans are unable to synthesize. We investigated clinical/laboratory factors associated with folate deficiency in tertiary care patients. We reviewed medical records of 1019 patients with serum folate <7.0 ng/mL, 301 patients with serum folate of 15 ng/mL, and 300 patients with serum folate >23 ng/mL. Serum prealbumin levels were subnormal in 54.8% of patients with serum folate <7.0 ng/mL. Vitamin B12, hemoglobin, and serum albumin levels were significantly lower in the <7.0 ng/mL folate group. In 62.4% of patients with serum folate <7.0 ng/mL, one or more markers of malnutrition were present. The low-folate group had a significantly higher prevalence of gastrointestinal (GI) disorders, sepsis, and abnormal serum creatinine level. There were no significant differences in the two groups regarding the prevalence of diabetes; behavioral/neurological disorders, including drug and alcohol abuse; bariatric surgery; or a diagnosis of malnutrition. The average body mass index (BMI) for the <7.0 ng/mL and 15 ng/mL folate groups was significantly different (28.89 and 28.31, respectively), although the difference does not appear to be clinically meaningful. The prevalence of folate deficiency depends on what is considered a normal serum folate level. Approximately 10% of tertiary care patients have levels <7.0 ng/mL and exhibit other markers of malnutrition. It is recommended that patients with GI disorders, chronic kidney disease, and sepsis be routinely tested for serum folate levels, before administration of vitamin supplements. Patients with serum folate levels <7.0 ng/mL should be evaluated for malnutrition, despite BMI >25. Folate supplementation should be administered only after excluding coexisting vitamin B12 deficiency.